2020
DOI: 10.3390/nu12072009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Feeding Efficiency and Hospital Mortality between Small Bowel and Nasogastric Tube Feeding in Critically Ill Patients at High Nutritional Risk

Abstract: Nasogastric tube enteral nutrition (NGEN) should be initiated within 48 h for patients at high nutritional risk. However, whether small bowel enteral nutrition (SBEN) should be routinely used instead of NGEN to improve hospital mortality remains unclear. We retrospectively analyzed 113 critically ill patients with modified Nutrition Risk in Critically Ill (mNUTRIC) score ≥ 5 and feeding volume < 750 mL/day in the first week of their stay in the intensive care unit (ICU). Age, sex, mNUTRIC score, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Therefore, our study was the first to demonstrate that mNUTRIC score, rather than APACHE II or SOFA score, is significantly associated with ICU mortality for adult patients with ARDS requiring PP therapy. As our previous study also demonstrated [ 8 , 9 , 10 , 11 ], mNUTRIC score is a useful tool to evaluate nutritional risk in critically ill adult patients admitted to medical ICUs.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Therefore, our study was the first to demonstrate that mNUTRIC score, rather than APACHE II or SOFA score, is significantly associated with ICU mortality for adult patients with ARDS requiring PP therapy. As our previous study also demonstrated [ 8 , 9 , 10 , 11 ], mNUTRIC score is a useful tool to evaluate nutritional risk in critically ill adult patients admitted to medical ICUs.…”
Section: Discussionmentioning
confidence: 90%
“…However, Reignier et al revealed a significant improvement in feeding volume after a feeding protocol implementation in ARDS patients required PP therapy [ 41 ]. Because our RICU has evaluated nutritional risk and implemented the feeding protocol within 24 h of admission for all critically ill patients since 2016 [ 8 , 9 , 10 , 11 ], feeding targets are monitored and titrated to the maximum volume, even for patients requiring PP therapy. Therefore, our study also revealed that the difference in EAR on each day ( Figure 2 ), rather than the average EAR in the first week of ICU admission, provides more information regarding mortality risk for patients receiving the feeding protocol.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations